Consequences of Labeling Terrorists in Papuan Armed Violence Groups: An Examining Belligerent Perspective on the Subject of International Law - Fakihudin, Rifki (Universitas Negeri Semarang, 2021)
The labeling of terrorists that the government has attached to the KKB in Papua has made this organization wanted by the TNI and POLRI. The eradication of terrorists is regulated in Law Number 5 of 2018 concerning the Eradication of Criminal Acts of Terrorism. This study aims to analyze the consequences of labeling KKB terrorists in Papua from a belligerent perspective according to international law. Belligerent is a rebel group that is recognized as a subject of international law. For this reason, this study uses a normative legal research method with a doctrinal approach. The legal materials used are primary and secondary legal materials using literature study analysis. The results show that terrorists can be categorized as non-state actors who are not legitimized under international law and can be considered unlawful belligerents when they participate directly in the war. Therefore, the status of KKB terrorists in Papua under international law can be considered civilians as long as they are not involved in the fighting. If KKB terrorists are involved in combat, then their legal status becomes unlawful belligerent.